(untitled) (Journal of Organizational Psychology, 2023)
This paper reviews employees’ resistance strategies to workplace bullying. The paper integrates the theoretical philosophies of Foucault’s (1977, 1982) power discourses, Scott’s (1985) resistance ideologies, and thirty-five in-depth interviews with employees working within the service sector, specifically, a college, motel, non-profit organization, and hospitals. The victims’ responses are thematically analyzed using a dialectic phenomenology paradigm to reveal a series of resistance responses ranging from retaliating, ignoring, quitting, avoiding, and successfully implementing anti-bullying interventions. In addition, interesting insights are proven on the detrimental impact of even non-confrontational resistance actions of employees to organizations. This study reinforces the importance of designing zero-tolerance bullying workplaces regardless of the products manufactured or services offered.